Green Purchase Intention of Indonesian Young Consumers: Extending VAB Framework - Fatya Alty Amalia; Adila Sosianika; Felicia Amanda Christabel (Journal of Marketing Innovation (JMI), 2021)
The study aims to investigate the determinants of green purchase intention of generation Y and Z in Indonesia, more specifically on the green straws. Quantitative methodology was carried out through disseminating the online survey and analyzing the collected used of PLS-SEM.  From 394 respondents, the findings showed the value-attitude-behavior (VAB) framework was successfully applied in this study. It meant perceived green value and green attitude significantly impacted on the green purchase intention. In addition, environmental concerns were proven to be the predecessor of the VAB framework as well. The moderating effect of gender only appeared on the relationships of perceived green value-green purchase intention and green attitude-green purchase intention; not on the environmental concerns-green purchase intention. From the theoretical perspective, this study contributes to the extension of the VAB framework through the inclusion of environmental concerns. From the managerial perspective, it provides the specific approaches for males and females consumer groups to awake their green purchase intentions.